2015
DOI: 10.1007/s00477-015-1036-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of a comprehensive assessment method of the environmental quality of soil in industrial and mining gathering areas

Abstract: Industrial and mining activities have been recognized as major sources of heavy metal contamination in soil. Here, we developed a comprehensive assessment method for the soil environment in industrial and mining gathering areas based on the pressure-state-response model. Using this method, we assessed the environmental quality of soil in a typical industrial and mining gathering area in Tianjin City, China. The results are as follows: (1) The comprehensive environmental quality index of the soil in the study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Rapid urbanization area is mostly located in mineral-rich regions, with high background values of metal elements. Ecological risk in these areas is strongly affected by human factors because of the high industrial and mining activities [7][8]. Contents, ecological effects, environmental effects, toxicology, and element background values of heavy metals should be considered for evaluating the ecological risk of rapid urbanization area.…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…Rapid urbanization area is mostly located in mineral-rich regions, with high background values of metal elements. Ecological risk in these areas is strongly affected by human factors because of the high industrial and mining activities [7][8]. Contents, ecological effects, environmental effects, toxicology, and element background values of heavy metals should be considered for evaluating the ecological risk of rapid urbanization area.…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…Detailed information about the spatial distribution of the regional soil environmental quality (SEQ) and pollution risks of heavy metals can provide fundamental information for regional environmental planning and environmental management. However, it is difficult to comprehensively assess SEQ for two reasons (Guan et al, 2016). One is for strong spatial variations of heavy metal content and other physical and chemical properties (Cai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Industrial and mining activities have always been leading sources of soil pollution [ 1 , 2 ]. In China, mining and industrial gathering areas have been established and rapidly developed across the country.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the mines and surrounding areas were identified as sources and heavy metals were considered the most serious pollutants. The spatial distribution [ 2 , 13 , 14 , 15 ], risk assessment [ 2 , 13 , 16 , 17 , 18 ], and mobility [ 19 , 20 ] of pollutants in soils also provided important information.…”
Section: Introductionmentioning
confidence: 99%